Efficiency of aerobic granulation technology in treating high strength soy sauce wastewater - Hasnida Harun,; Aznah Nor-Anuar,; Zaini Ujang,; Inawati Othman,; Nor Hasyimah Rosman, (Universiti Kebangsaan Malaysia, 2014)
The present study investigated the efficiency of aerobic granular sludge (AGS) technology in treating effluent from soy sauce industry which is categorized as a high strength wastewater. The combination of anaerobic and aerobic granulation technology in SBR system was used in this study which was efficiently treated COD from the soy sauce wastewater where 87% of removal was achieved. Ammonia and colour was removed at a maximum of 87 and 76%, respectively, in the SBR system. Matured, dense and compact granules with 2.5 mm in diameters were developed with a good settling velocity (45 m/h) and 28 mL/gSS of sludge volume index (SVI). Hence, AGS technology was proven as an excellent treatment for soy sauce wastewater for being discharge into the environment, as the effluent was treated in one biological reactor with high hydraulic and organic loadings besides less production of sludge. In this study, the capabilities of AGS technology in treating relatively higher concentration of organic impurities present in the soy sauce wastewater were demonstrated.